Comment: The Interaction Between Metaphor and Emotion Processing in the Brain. (July 2016) - Aziz-Zadeh, Lisa; Gamez-Djokic, Vesna
It has been argued that metaphor and emotion processing are tightly linked together. Here we explore whether neuroscientific evidence supports this claim.